2013
DOI: 10.1186/2049-1891-4-51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese herbal medicine on plasma glucose, protein and energy metabolism in sheep

Abstract: BackgroundThe use of antibiotics in animal diets is facing negative feedback due to the hidden danger of drug residues to human health. Traditional Chinese herbal medicine has been used to replace antibiotics in the past two decades and played an increasingly important role in livestock production. The present study was carried out to assess the feeding effects of a traditional nourishing Chinese herbal medicine mixture on kinetics of plasma glucose, protein and energy metabolism in sheep. Ruminal fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…the enrichment of exhaled 13 CO 2 that derived from leucine oxidation. However, the numerical values of WBPS observed with the [ 2 H 5 ]Phe model in this study were lower than those observed with the [1-13 C]leucine model (calculated from plasma enrichment of α-[1-13 C]ketoisocaproic acid, the true precursor of intracellular leucine metabolism) in sheep in our previous work(Liang et al, 2013).These results accord with the observation ofAl-Mamun, Ito, Sato, Fujita, and Sano (2004) who compared the [ 2 H 5 ]Phe model with the [1-13 C]leucine method to determine protein metabolism in sheep.…”
contrasting
confidence: 87%
See 4 more Smart Citations
“…the enrichment of exhaled 13 CO 2 that derived from leucine oxidation. However, the numerical values of WBPS observed with the [ 2 H 5 ]Phe model in this study were lower than those observed with the [1-13 C]leucine model (calculated from plasma enrichment of α-[1-13 C]ketoisocaproic acid, the true precursor of intracellular leucine metabolism) in sheep in our previous work(Liang et al, 2013).These results accord with the observation ofAl-Mamun, Ito, Sato, Fujita, and Sano (2004) who compared the [ 2 H 5 ]Phe model with the [1-13 C]leucine method to determine protein metabolism in sheep.…”
contrasting
confidence: 87%
“…A number of isotope dilution methods using different amino acid isotopes have been applied to estimate the WBPS in experimental animals. Among the isotopes, [1-13 C]leucine is the most widely used amino acid isotope (Krishnamurti & Janssens, 1998;Lapierre et al, 2002;Liang et al, 2013). In our current experiment, the isotope As expected, the results from this study demonstrated that the Chinese herbal medicine could accelerate turnover and oxidation of plasma amino acids as well as enhance protein metabolism in sheep.…”
Section: Kinetics Of Protein Metabolismsupporting
confidence: 72%
See 3 more Smart Citations